Zootherapeutic practices in the Amazon Region: chemical and pharmacological studies of Green-anaconda fat (Eunectes murinus) and alternatives for species conservation - Ferreira Abrão, Camila; Ribeiro de Oliveira, Danilo; Passos, Paulo; Rodrigues Pereira Freitas, Carla Valéria; Ferreira Santana, Amanda; Lopes da Rocha, Marilene; Ribeiro da Silva, Antonio Jorge; Tinoco, Luzineide Wanderley (Ethnobiology and Conservation, 2021)
The treatment of diseases with animal resources or their derivatives is a traditional practice worldwide, representing a wide field of research for the elaboration of strategies of management and conservation of the fauna, and contributing to the search for sustainable therapy alternatives. This study presents the therapeutic applications of animal fats to the treatment of several diseases in Pimenteiras do Oeste, state of Rondônia, Brazil. Twelve animals including: mammals, fishes, reptiles and birds are reported as a source of medicinal lard for the treatment of respiratory illnesses (asthma, flu, bronchitis, cough), rheumatism, and earache and as a healing agent (dislocation and wounds). The ethnopharmacological focus of the study was on Green-anaconda fat (Eunectes murinus), which stands out for its frequent local use and the lack of previous chemical studies. The chemical composition of E. murinus fat was analyzed by gas and liquid chromatography, both coupled to mass spectrometry. The main fatty acids identified were oleic, linoleic and palmitic acids, which were also predominant in the composition of the triglycerides. Pharmacological analysis of Green-anaconda fat showed a significant anti-inflammatory effect, which is related to its use by traditional communities. Having confirmed the pharmacological potential of Green-anaconda fat, its fatty acid composition was used as a parameter in the search for vegetable oils from the Amazon Region with a similar composition. This comparative analysis can be of help by proposing therapeutic alternatives for the Amazonian population. The use of plant sources can contribute to the conservation of the aforementioned species.